2016
DOI: 10.29302/oeconomica.2016.18.1.4
|View full text |Cite
|
Sign up to set email alerts
|

"The Degree Of Satisfaction Perceived By Healthcareservices Consumers In State Hospitals - Case Studyemergency County Hospital From Alba Iulia "

Abstract: The paper investigates the degree of satisfaction of the patients that accessed the medical services provided by the Emergency County Hospital from Alba Iulia. The hey factors considered important in establishing the degree of satisfaction were the following: the endowment with new generation of portable medical equipment (ultrasound machine, portable oxygen, resuscitation equipment); the endowment with new generation of fixed medical equipment (ray machine, CT); the hospital furniture; the endowment with non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
1
Order By: Relevance
“…According to Chiu and Wu (2002), it includes the affective and cognitive components of service quality. Several studies have shown that affective and cognitive responses play an essential role in determining customer behaviors (Andreea and Ruxandra, 2016;Um and Lau, 2018). Therefore, it is necessary to examine both affective and cognitive perceptions to influence the understanding of service quality (Hartono and Raharjo, 2015).…”
Section: Developing the Hypothesismentioning
confidence: 99%
“…According to Chiu and Wu (2002), it includes the affective and cognitive components of service quality. Several studies have shown that affective and cognitive responses play an essential role in determining customer behaviors (Andreea and Ruxandra, 2016;Um and Lau, 2018). Therefore, it is necessary to examine both affective and cognitive perceptions to influence the understanding of service quality (Hartono and Raharjo, 2015).…”
Section: Developing the Hypothesismentioning
confidence: 99%
“…Memnuniyet, "müşterilerin tüketimden sonra edindikleri deneyimlere dayalı oluşan duyguları"; hasta memnuniyeti de, "hastaların beklentilerinin karşılanıp karşılanmadığını görmek için sürecin tıbbi sonucunu analiz ettikten sonra yaptıkları yargının sonucu" olarak tanımlanmaktadır (Andreea & Ruxandra, 2016). Andaleeb vd., (2007), hastaların sağlık hizmetlerinden duydukları memnuniyet düzeylerinin ölçülmesinin hizmet kalitesi ve kurumsal imaj açısından çok önemli olduğunu belirtmişlerdir.…”
Section: Hasta Memnuniyetiunclassified
“…However, Chiu and Wu (2002) (perspectives of attitude) include the cognitive and affective components of service quality. A number of studies have suggested that both affective and cognitive responses play an important role in determining their behaviors (Um and Lau, 2018; Muntean and Ruxandra, 2016). Khalid and Helander (2006) suggest cognition is formed of beliefs and knowledge, while affective responses involve emotions, sentiments and attitudes.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%